2017
DOI: 10.1039/c6cy02410f
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing designed mutants: a valuable strategy for computer-aided laccase engineering – the case of POXA1b

Abstract: The Q3broad specificity of laccases, a direct consequence of their shallow binding site, makes this class of enzymes a suitable template to build specificity toward putative substrates.Please check this proof carefully. Our staff will not read it in detail after you have returned it.Translation errors between word-processor files and typesetting systems can occur so the whole proof needs to be read. Please pay particular attention to: tabulated material; equations; numerical data; figures and graphics; and ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In another study, K m values were reported for the activity of CuL toward phenols, acids, ketones, amines and phosphates 29 . Structure-guided computational design of laccases using both classical and quantum mechanical approaches is a viable and very useful path to discover new proficient laccases for turnover of specific substrates 30 , 31 . Quantitative models trained on actual turnover data would in principle offer more predictive accuracy, but depend critically on systematic experimental data on substrate turnover rates for their validation.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, K m values were reported for the activity of CuL toward phenols, acids, ketones, amines and phosphates 29 . Structure-guided computational design of laccases using both classical and quantum mechanical approaches is a viable and very useful path to discover new proficient laccases for turnover of specific substrates 30 , 31 . Quantitative models trained on actual turnover data would in principle offer more predictive accuracy, but depend critically on systematic experimental data on substrate turnover rates for their validation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a disadvantageous ΔE° between enzyme and substrate, all the tested laccases proved to be able to oxidize aniline, although with different efficiency (Figure ). This result further highlights how laccase reactivity is an intricate multidimensional problem in which the Electron Transfer driving force is an important factor depending on not only T1 E°, but also on the right pose of the substrate within the binding pocket. Particularly relevant is the difference observed between rPOXA1b and 1H6C, where the latter enzyme, although characterized by a higher redox potential with respect to the wild type, displayed the worst performance in aniline oxidation.…”
Section: Resultsmentioning
confidence: 66%
“…The above results suggest that the performance of the mutants is not proportional to the number of substitutions. Interestingly, the kinetics performance of the laccase variants towards ABTS was considerably enhanced, while their affinity constants were similar to those of other fungal laccases [ 17 , 30 ].…”
Section: Resultsmentioning
confidence: 66%